Impact on quality of life among health care workers: a case-control study of COVID-19 pandemic situation - Babu, Surendra; Nagoor, Khadervali; Narayana, Mood; Bala, Sudha; Animalla, Venkatesham (International Journal Of Community Medicine And Public Health, 2023)
Background: Quality of Life (QoL) as an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. Methods: A Case-control study was conducted to assess the QoL among health care workers (HCW) during the Covid-19 Pandemic and to compare QOL in cases and controls among HCW. The sample size was calculated to be 98 in each group comes around 196. QOL was assessed by using WHOQOL-BREF scale. The QoL comparison in both Covid-19 positive and negative and its association was done by mean and standard deviation with correlation coefficient using unpaired T test. Results: Among 196, majority 157 (79.2%) were doctors and 39 (19.8%) were other health care providers like lab technicians and nursing staff. The health care workers with COVID-19 positive were had low QoL than the negative with respect to physical (46.90±9.60 vs 59.01±15.60), psychological (44.51±7.44 vs 51.13±15.68), social (39.82±15.98 vs 56.11±23.92), and environmental (48.33±10.28 vs 57.57±20.22) domains and all the domains showing highly statistically significant result with the P-value <0.001. The correlation coefficient between four domains was statistically significant and with overall QOL and satisfaction on health. Conclusions: The QoL was poor among COVID-19 positive patients compared to negative with respect to physical, social, psychological, and environmental and age, marital status and occupation during the covid-19 pandemic.